Tohu Wabohu dan Creatio ex Nihilo: Tafsir Kejadian 1:1-2 Sebagai Perspektif Memahami Realitas Anomali - Agus Kriswanto (Sekolah Tinggi Teologi Sriwijaya, 2020)
Some interpreters have argued that the doctrine of creatio ex nihilo cannot be based on the reading of Genesis 1: 1-2. Genesis 1: 1-2 shows that the earth which was in a state of tohu wabohu (chaos) was the initial condition of pre-creation. Chaos was then organized into a new order. This paper argues that Genesis 1: 1-2 can be read, both as creation ex nihilo as well as transformation from chaos into harmony. This research is a qualitative research with descriptive-analytical method. The description of the meaning of Genesis 1: 1-2 is done through syntactic analysis, the literary context of Ancient Near Eastern cosmogony, and the relation of Genesis 1 to the world view of the priesthood. The results of this study indicate that although Genesis 1: 1-2 echoes the expression of ancient chaos, it has been placed as a consequence of God's creative act. The creation ex nihilo of heaven and earth, carries the risk of chaos which is further arranged by God into a good order. In addition, if it is related to the worldview that forms the basis of ritual, Genesis 1: 1-2 not only gives a picture of the origin of the world, but also provides a perspective to understand reality, both harmony and anomalies.